Allometric study of functional fitness of children and adolescents in a rural area of Mozambique.DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n5p507 - Luciano Basso; Antonio Prista; Leonardo Nhantumbo; Silvio Saranga; José Maia (Universidade Federal de Santa Catarina, 2012)
Few studies in Africa have investigated the physical performance of children using the allometric method. This study evaluated the functional fitness of children and adolescents in a rural area of Mozambique using the contrast between theoretical models and empirical allometric coefficients. Height and weight were measured and functional fitness was assessed using the AAHPERD, EUROFIT and Fitnessgram tests. The allometric equation Y=aXb, was used. In addition to descriptive statistics, factorial ANOVA was used to test differences of body size and functional variables between sexes and age groups. An extension of the allometric equation based on ANCOVA was used after proper logarithmic transformation of all variables of interest. Mean height and weight increased with age and were significantly associated with age and sex. Functional fitness increased with age, and mean results were higher for boys. Allometric coefficients were different from those expected according to theory, and girls had higher coefficients in almost all tests. A marked sexual dimorphism was seen in functional fitness results according to age. Empirical coefficients were different from those expected according to theory, which demonstrated the absence of the presumed geometric similarity. Girls had higher coefficients than boys in all fitness tests.